Pengaruh saving motives, kompetensi dan pengalaman positif terhadap keputusan membeli asuransi dengan kecenderungan membeli sebagai variabel mediasi - Kristina Mersis; Mellyza Silvi (Journal of Business & Banking, 2019)
The aim of this study was to examine the effect of saving motives, competency, and positive experience on insurance purchasing decision with the intention to purchase as a mediating variable. The study took 295 respondents which were taken based on the criteria such as having insurance and being a decision maker to buy insurance and living in Surabaya, Gresik, and Tuban. The data were analyzed using a Partial Least Square Structural Equation Modeling (PLS-SEM) by using PLS 6.0 program. The results showed that saving motives, competency and positive experience have a significant positive effect on insurance purchasing decision, while the inclination to purchase can mediate the effect of competency and positive experience on insurance purchasing decision.